Federal Budget and State Fiscal Policy: Macroeconomic Adaptation until 2025 - Mikhail E. Kosov; Alla Yu. Chalova; Ravil G. Akhmadeev; Ekaterina V. Golubtsova (Финансовый журнал, 2023)
The article examines the modern concept of the state fiscal policy in Russia and the possibilities of its implementation through the federal budget in the face of new global challenges. To this end, the authors assessed the resource base of the federal budget of the Russian Federation, as well as the adequacy of measures of fiscal regulation of the current economic situation. In this regard, the authors evaluated the feasibility of the initial macroeconomic indicators underlying the parameters of the federal budget for 2023–2025, primarily its revenues, and the risks of their possible change. The authors associate the key risks of failure to achieve the stated goals of the budget and tax policy for the period 2023–2025 with a sharp reduction in the resource base of the federal budget, especially its oil and gas revenues in the context of worsening geopolitical tensions and increasing sanctions pressure on the Russian Federation. The study focuses on the justification of approaches to minimize the negative consequences of external shocks both for the subjects of the Russian economy and for public finances. In the course of the study, the authors used the methods of statistical data processing, factor modeling, regression analysis and expert evaluation. The scientific novelty of the study lies in the assessment of the impact of new global challenges on the balance of the Russian federal budget and substantiation of approaches to transform fiscal regulation measures in response to these challenges. The practical significance of the study lies in the possibility of using its results in the development of state fiscal policy in the medium term under the conditions of dramatic changes in the scenario conditions of formation of the federal budget.